Implementasi Penerapan Teori Konstruktivisme Dalam Proses Pembelajaran Di Sekolah Dasar - Yunela Fitri (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
Constructivism learning theory is an educational theory that puts forward the improvement of logical and conceptual development of learning. Constructivism theory believes that students construct knowledge for themselves. Constructivism is the cornerstone of contextual approach thinking, namely that knowledge is built not a set of facts, concepts, or rules that are ready to be remembered. Students must construct that knowledge and give meaning through real experience. Students need to be accustomed to solving problems, finding something useful for themselves. Students must construct knowledge in their own minds. Critical thinking is an effort made by someone to check the truth of an information using the availability of evidence, logic, and awareness. Critical thinking skills are students' cognitive processes in analyzing systematically and specifically the problems encountered, as well as identifying and reviewing information in order to plan problem solving strategies